Converting a Story from Students’ Own Language in English to Increase Speaking Ability - Ismail, Ismail (Universitas Muhammadiyah Enrekang, 2019)
This present study required to expose the contribution of English Gossip Magazine as a resource of learning material activities to increase the students’ enthusiasm in speaking skill in EFL classes. This study was carried out on two groups–experimental and control groups- each of which consists of 15 students. The students were preliminary class students of English Education Department at STKIP Muhammadiyah Enrekang, Indonesia. Before the treatment, a pretest was administered to both groups. The results of the pretest demonstrated that there was not significant difference between the control and the experimental group. Throughout the study, the experimental group was taught speaking through English Gossip Magazine materials taken from webzines, and the control group was taught through a conventional method. The result indicates that the use of the English Gossip Magazine as a resource of learning material activities could significantly contribute to increase the students, enthusiasm in speaking skill in EFL classes.